Peningkatan Pendapatan Pedagang Siomay - Widanarni Pudjiastuti; Evi Maria (Jurnal ABM Mengabdi, 2017)
Siomay is one of alternative food besides rice, snacks / distractions such as rujak, batagor which is now an alternative that is a trend and popular community, especially young people. Partners of this IbM program are the father of Suparwan and Sudarsono. The problem was from the aspect of production is the availability of raw materials influenced by weather factors and equipment to process raw materials that have not been adequate. While from the aspect of managerial capability is the labor that is only done alone and the ability to process and perform financial records. The solution given to partners for production aspects is the provision of equipment to store the main raw materials, especially fish (frezeer) so that the main raw materials are always available and not depending on the weather, milling and mixing of raw materials. It is also proposed to add manpower that serves to assist the production process and to open a new place of business. For the managerial aspect that is given training on the layout of the place of production, entrepreneurship and marketing and recording of simple financial statements. It is expected that with this IbM program, the two partners can increase sales turnover, bringing the impact of the growing siomy traders that become partners can create new jobs, so they can compete with similar business.